Mental health of persons deprived of liberty - a review of issues and systemic challenges - Koguc, Karolina; Sikora, Gabriela; Woźniak, Martyna; Kutnik, Karolina; Kusibab, Karolina; Czechowski, Michał; Sajda, Małgorzata; Gunia, Katarzyna; Słomianny, Marcela; Kolada, Karolina (Quality in Sport, 2025)
Introduction: The global prison population is rising at an alarming rate. The unique conditions within correctional facilities, combined with inmates’ complex personal histories, make prisoners more vulnerable to mental health problems than the general population. Methodology: A review was conducted using PubMed, Google Scholar and ResearchGate. Search terms included: prisoner mental health, prisoner needs, women in prison, incarceration and prison mental health care. A review of studies published between 2010 and 2025 was conducted. Results: The most prevalent mental illnesses among prisoners are depression, anxiety disorders, bipolar disorder, and schizophrenia spectrum disorders. Inmates are at an increased risk of self-harm and suicide. The widespread use of psychoactive substances—often exacerbating mental health conditions—remains a serious concern. Women and non-heteronormative individuals in prison show increased susceptibility to mental health issues. Conclusions: Correctional facilities should prioritize the provision of mental health services and implement routine psychological screenings. Prisons must be adapted to accommodate the specific needs of women, older individuals, and LGBTQ+ inmates, ensuring inclusive and appropriate care.